Geographical Information System (GIS) for relationship between dengue disease and climatic factors at Cheras, Malaysia = Perhubungan Antara Kes Denggi dan Faktor Iklim Menggunakan Sistem Maklumat Geografi di Cheras, Malaysia - Mustafa, Ahmad Dasuki; Azid, Azman; Juahir, Hafizan; Yunus, Kamaruzzaman; Zainal Abidin, Ismail; Sulaiman, Nur Hishaam; Azizi, Mohammad; Osman, Mohamad Romizan; Kamarudin, Mohd Khairul Amri; Gasim, Muhammad Barzani (Universiti Kebangsaan Malaysia (UKM), 2015)

(untitled)
The Geographical Information System (GIS) was utilized to generate dengue distribution cases and its correlation to the climatic factors in Cheras, Kuala Lumpur, Malaysia. The data were provided by Dewan Bandaraya Kuala Lumpur (DBKL). The data was integrated with Kuala Lumpur map to graphically present information about the areas which been hit by the dengue outbreak through a graphic display. The analysis using focused on overlay, buffer creating, and query builder. The statistical analysis such as linear regression is undertaken to show the correlation between dengue diseases with the climatic factors that is rainfall, temperature and relative humidity for the year 2008, 2009, 2010, and 2011. The study found that there is no correlation between disease incidence and total rainfall (R2=0.057). Thus, it can be concluded that the climatic factors were not contributed to the dengue cases. Through this research, highly expect that the dengue distribution map had been developed and can be used by the authorities to analyzing the dengue disease pattern by related with the climatic factors.